Colouterine Fistula (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Colouterine fistula is a extremely rare condition .It may be congenital,iatrogenic or secondary to malignancy.Here we report a congenital type of colouterine fistula with successful primary repair without hysterectomy in a nulliparous woman.Usually treatment of a parous women is hysterectomy followed by repair of rent in the colon.J Bangladesh Coll Phys Surg 2017; 35(1): 31-33